Heat Template Generator in Openstack (International Journal of Engineering and Computer Science, 2015)
Cloud computing seems to be recent technology, but the term’s origin is quite unclear. In this paper, we present an overview of a project namely Heat Template Generator in Openstack. Our aim is to equip our readers with the overall functioning of the Heat component of Openstack and help them to understand the current features that are supported by the same. We then also briefly discuss about what is the current scenario about template writing and how this project will improves the productivity. We conclude by providing brief account of how this Template Generator is future of Orchestration in cloud computing.